KAJIAN INTERDISIPLINER: KONSEP EKONOMI INDONESIA DITINJAU MELALUI PENDEKATAN HUKUM ISLAM DAN HUKUM POSITIF - Alamudi, Ichwan Ahnaz (STIS Darussalam Bermi, 2022)
This article is motivated by the sound of the 1945 Indonesian constitution Article 33 initiated by the founding fathers contains the philosophy of togetherness and the principle of family that is the cornerstone of the Indonesian economy. The realization of Islamic Economics in Indonesia has had a major impact on efforts to improve the economic life of the community, as well as provide education to the community in the economic system using a non-ribawi system. This article uses a qualitative descriptive approach that is more specific to the data of the library or library research. In this paper the author meghasilkan that Syar'i law khitab (decree) of God related to the act of mukallaf in the form of demands, choices and provisions and each claim contains taklif (legal burden) which in this case is human mukallaf. Furthermore, the 1945 Indonesian constitution Article 33 paragraph 2 is an important pillar in the development of economic law in Indonesia which determines, “the branches of production that are important to the state and that control the livelihood of many people are controlled by the state. So, in this paragraph is a constitutional mandate that should be run by the government. Keywords: Economy, Islamic Law, Positive Law.